The Influence of Transformational Leadership Style On The Performance of State Civil Apparatus In City Government X - Jopinus Saragih (Return : Study of Management, Economic and Bussines, 2024)
Leadership plays a crucial role in determining the effectiveness of organizations, including government institutions. State Civil Servants (ASN) within the government are pivotal in administering governmental affairs and delivering public services to citizens. Hence, it is imperative to address the performance of ASN in City Government. This study aims to examine the influence of transformational leadership styles on the performance of state civil servants in City Government X. Employing quantitative research methods, data were collected through surveys utilizing questionnaires and literature reviews. Subsequently, the gathered data underwent analysis via regression tests conducted using the SPSS software. The findings of the research indicate a significant impact of transformational leadership patterns on the performance of ASN. Therefore, leaders within City Government X should adopt dimensions such as ideal influence, intellectual stimulation, individual consideration, and inspirational motivation to enhance the performance of ASN.